The importance of mastering foreign languages in developing hospitality and tourism industries - Acep, Unang, Rahayu (Journal of Business on Hospitality and Tourism, 2015)
This study aims at offering some thoughts that cultural differences influence a great deal in hospitality and tourism industries. In Indonesia English is a second language whereby occupational background in the past still dominates our language structure. Indonesia was occupied by the Dutch for 3 and half decades then by the Japanese for 3 and half years. Lacking of vocabulary items, Indonesian Language still use foreign languages such those borrowed from Dutch, English, Italian, Portuguese and Arabic.Cultural differences also influences Indonesian way of using the English expressions at hospitality industries. Mastering foreign languages is very important in developing hospitality industries in Indonesia. The main findings of my research are : those motivated students learn foreign languages better, those having good learning strategies master foreign languages better, and those mastering foreign languages work successfully at hospitality and tourism industries.